Breeding tropical carrots (Daucus carota) for enhanced nutrition and high temperature stress - SAHA, SWATI; KALIA, PRITAM; SUREJA, AMISH KUMAR; SARKAR, S (The Indian Journal of Agricultural Sciences, 2016)
Carrot (Daucus carota L.) is a globally important vegetable crop providing a source of important nutritional compounds through carotenoid content whilst adding flavour and texture to many diets. Temperature influences growth, yield and quality of carrots in many different ways. The influence of varying temperatures on yield and quality parameters of carrots has been a topic for research during the last three decades. An attempt was done to analyze inbreds for quantitative and qualitative traits for the selection of inbreds for high temperature stress. The inbreds showed variation in plant weight, foliage weight, root weight, root length and root girth with average of 233.71g, 74.16g, 164.13g, 21.62 cm, whereas root girth ranged from 4.77-3.70 cm respectively. Anthocyanin content estimated to be highest in dark purple black inbred line IPC-126 (333.81 mg/100g) while the total carotenoid content was highest in root tissue of IPC-124 (14.46 mg/100g). The lycopene content ranged from 0.50 mg/100g (IPC-126) to 11.85 mg/100g (IPC-124). TSS ranged from 6.7 to 10.48 °Brix. Some inbreds performed well under extreme high temperature without affecting any quality attributes. Such inbreds could be selected for further breeding program. The results of our study will help in development of high quality superior hybrids using the promising inbreds in tropical carrot.